The Importance of Connexin 43 in Enamel Development and Mineralization - Al-Ansari, Sali; Jalali, Rozita; Plotkin, Lilian I.; Bronckers, Antonius L. J. J.; DenBesten, Pamela; Zhang, Yan; Raber-Durlacher, Judith E.; de Lange, Jan; Rozema, Frederik R. (Frontiers in Physiology, 2018)
During enamel development, formation of hydroxyapatite crystals and regulation of pH in the enamel matrix require massive transport of ions. Both ameloblasts and adjacent dental epithelial cells in the stellate reticulum co-express several transmembrane cotransporters/ion-exchangers for transport of ions across plasma membranes. Gap junctions (GJs) enable intercellular exchanges of ions between neighboring cells. This suggests that the ameloblasts and other cell layers of the enamel organ, form a functional unit. During the bell stage of tooth formation, the non-ameloblast dental epithelium highly expresses the Na-K-Cl cotransporter (Nkcc1). Nkcc1-null mice are associated with enamel hypomineralization and increased expression of GJ protein connexin 43 (Cx43), suggesting that reduced ion transport in the Nkcc1-null mouse is in part compensated by increased intercellular ion transport through GJs. To understand the role of GJs in ion transport and its effect on pH regulation, we examined in a mouse strain in which Cx43 was ablated selectively in DMP1 expressing cells (Cx43flox/flox mice crossed with DMP1-8kb-Cre mice), including ameloblasts. Micro-CT analysis showed that the mineral density at late maturation stage incisal enamel of the Cx43-null mice was 10% less than in controls, whereas that in dentin was unchanged. Maturation stage ameloblasts of mice lacking the pH regulating sodium/bicarbonate transporter NBCe1 (Nbce1-null), or chloride channel Cftr (Cftr-null) were found to have increased Cx43-immunostaining. These results support the possibility that GJs in the ameloblast–papillary complex at the maturation stage contribute to ion transport by enabling passage of ions directly from cells of the papillary layer into ameloblast layer. Increasing the number of GJs may partly compensate the reduction of ion-cotransporters and ion exchangers in dental epithelium.